2015
DOI: 10.1103/physreva.91.012301
|View full text |Cite
|
Sign up to set email alerts
|

Mutual information as an order parameter for quantum synchronization

Abstract: Spontaneous synchronization is a fundamental phenomenon, important in many theoretical studies and applications. Recently this effect has been analyzed and observed in a number of physical systems close to the quantum mechanical regime. In this work we propose the mutual information as a useful order parameter which can capture the emergence of synchronization in very different contexts, ranging from semi-classical to intrinsically quantum mechanical systems. Specifically we first study the synchronization of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(130 citation statements)
references
References 28 publications
(63 reference statements)
3
127
0
Order By: Relevance
“…Recent work on coupled quantum van der Pol oscillators has suggested that there may be an intimate connection between the emergence of synchronization in coupled quantum oscillators and the behavior of the mutual information [8,15,19] and it has even been suggested that mutual information could serve as an order parameter for synchronization [15].…”
Section: Mutual Information and Entanglementmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent work on coupled quantum van der Pol oscillators has suggested that there may be an intimate connection between the emergence of synchronization in coupled quantum oscillators and the behavior of the mutual information [8,15,19] and it has even been suggested that mutual information could serve as an order parameter for synchronization [15].…”
Section: Mutual Information and Entanglementmentioning
confidence: 99%
“…Studies of synchronization effects in the quantum regime have largely concentrated on the behavior of simple model systems such as van der Pol oscillators [7,9,10,12,15,17,19,21] (together with closely related models [22]), though a number of other systems including atomic ensembles [13,16] and optomechanical oscillators [5,6,12,18] have also been investigated. In this article we investigate synchronization in a very different model system consisting of two weakly coupled micromasers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutual information and specific correlations have been used, not only as a signature of dynamical alignment of quantum systems, but also to evaluate the degree of synchronization [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, quantum strategies have been exploited to improve the accuracy of clock synchronization. A few quantum clock synchronization (QCS) proposals [5][6][7][8][9][10][11][12][13][14][15][16] and experiments [17] are reported. It is shown that the schemes based on quantum mechanics can gain significant improvements in precision over their classical counterparts.…”
Section: Introductionmentioning
confidence: 99%